Revisiting COVID-19 policies: 10 evidence-based recommendations for where to go from here. PUBLISHED VERSION: https://doi.org/10.1186/s12889-021-12082-z - Daniel T. Halperin; Norman Hearst; Stephen Hodgins; Robert C. Bailey; Jeffrey D. Klausner; Helen Jackson; Richard Wamai; Joseph A. Ladapo; Mead Over; Stefan Baral; Kevin Escandón; Monica Gandhi (2021)
Background: Strategies to control coronavirus 2019 disease (COVID-19) have often been based on preliminary and limited data and have tended to be slow to evolve as new evidence emerges. Yet knowledge about COVID-19 has grown exponentially, and the expanding rollout of vaccines presents further opportunity to reassess the response to the pandemic more broadly.Main text: We review the latest evidence concerning 10 key COVID-19 policy and strategic areas, specifically addressing: 1) the expansion of equitable vaccine distribution, 2) the need to ease restrictions as hospitalization and mortality rates eventually fall, 3) the advantages of emphasizing educational and harm reduction approaches over coercive and punitive measures, 4) the need to encourage outdoor activities, 5) the imperative to reopen schools, 6) the far-reaching and long-term economic and psychosocial consequences of sustained lockdowns, 7) the excessive focus on surface disinfection and other ineffective measures, 8) the importance of reassessing testing policies and practices, 9) the need for increasing access to outpatient therapies and prophylactics, and 10) the necessity to better prepare for future pandemics.Conclusions: While remarkably effective vaccines have engendered great hope, some widely held assumptions underlying current policy approaches call for an evidence-based reassessment. COVID-19 will require ongoing mitigation for the foreseeable future as it transforms from a pandemic into an endemic infection, but maintaining a constant state of emergency is not viable. A more realistic public health approach is to adjust current mitigation goals to be more data-driven and to minimize unintended harms associated with unfocused or ineffective control efforts. Based on the latest evidence, we therefore present recommendations for refining 10 key policy areas, and for applying lessons learned from COVID-19 to prevent and prepare for future pandemics.